2021
DOI: 10.1038/s41598-021-98966-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immune-related subtypes of colorectal cancer to improve antitumor immunotherapy

Abstract: Immunotherapy involving immune checkpoint inhibitors (ICIs) for enhancing immune system activation is promising for tumor management. However, the patients’ responses to ICIs are different. Here, we applied a non-negative matrix factorization algorithm to establish a robust immune molecular classification system for colorectal cancer (CRC). We obtained data of 1503 CRC patients (training cohort: 488 from The Cancer Genome Atlas; validation cohort: 1015 from the Gene Expression Omnibus). In the training cohort,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Immunoscore has been constructed to predict CRC prognosis using algorithms such as CIBERSORT [ 17 ] and ESTIMATE [ 18 ]. Previous studies reported better survivals in CRC patients with a low immunoscore or in an immune-activated subclass.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoscore has been constructed to predict CRC prognosis using algorithms such as CIBERSORT [ 17 ] and ESTIMATE [ 18 ]. Previous studies reported better survivals in CRC patients with a low immunoscore or in an immune-activated subclass.…”
Section: Resultsmentioning
confidence: 99%
“…Given the oncogenic role of PBK/TOPK in the process of tumorigenesis and tumor progression, it is interesting to find that high expression of PBK/TOPK correlates with an improved prognosis in colon cancer. Since tumor infiltrating immune cells contributes to determining the prognosis of colon cancer [ 60 , 61 ], we analyzed the changes in immune profiles including immune cell composition and inflammatory signatures. High PBK/TOPK expression in colon cancer was correlated with an increased infiltration level of cytotoxic immune cells, whereas activated CD8+ T- and NK-cell-infiltrated tumors also exhibited decreased infiltration of Treg cells and M2 macrophages that have immunosuppressive roles in TME.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al. ( 33 ) analyzed data from 488 patients with CRC from the TCGA-COAD dataset (training cohort) and from 1,015 in the GSE39582 ( 61 ), GSE14333 ( 63 ), and GSE17538 ( 65 ) datasets (validation cohorts). They identified immune-related immune-activated, immune-suppressed, and non-immune CRC subtypes using the NMF algorithm based on the top 150 exemplar genes in immune profiles.…”
Section: Introductionmentioning
confidence: 99%